Azide derivatized anticancer agents of vitamin K-3: X-ray structural, DSC, resonance spectral and API studies - Badave, Kirti D.; Patil, Yogesh; Gonnade, Rajesh G.; Srinivas, Darbha; Dasgupta, Rajan; Khan, Ayesha A.; Rane, Sandhya (Journal of Molecular Structure, 2011)
Compound 1 [1-imino (acetyl hydrazino)-Vitamin K-3], displays valence tautomerically related electronic isomers as Form land Form II. Form I exhibits 2D packing fragment with 1D ribbon chains of N-H center dot center dot center dot O hydrogen bonds and shows EPR silent features. While Form II is EPR active and exhibits biradical nature with double quantum transitions at g = 2.0040. H-1 NMR of compound 2, [1-imino (hydrazino carboxylate)-Vitamin K-3] and Form II exhibit pi delocalization via resonance assisted H-bonding [RAHB] effect compared to Form I. Molecular interactions in Form I and II are visualized by DSC. The electronic structures of compounds 1 and 2 have been correlated to their API values by measuring anticancer activities, mitochondrial potentials and DNA shearing patterns. Form II and compound 2 indicate mitochondria mediated apoptosis (similar to 75% cell death) while Form I causes 35% cell death. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anticancer agents; API (Active Pharmaceutical Ingredients); Electronic isomers; RAHB (resonance assisted H-bonding); Vitamin K-3

Synthesis and biological evaluation of some bicyclic [2-(2,4-dimethylphenylthio)phenyl] aniline and its amide derivatives as potential antitubercular agents - Patil, Yogesh; Shingare, Ramesh (Journal of Chemical Sciences, 2018)
In the present investigation, a series of bicyclic [2-(2,4-dimethylphenylthio)phenyl] aniline analogues were synthesized and characterized by IR, NMR (1H and 13C) and mass spectra. All newly synthesized 15 compounds were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra in both active and dormant state using an established XTT Reduction Menadione assay (XRMA). The titled compounds exhibited minimum inhibitory concentration (MIC90) ranging from 0.05 to >30 (μg/mL). The potent four compounds were further evaluated in THP-1 infection model where they demonstrated significant antitubercular activity. All the ex vivo active were further evaluated for cytotoxic activity against THP-1, MCK7 and HeLa cell lines in order to check selectivity index. All compounds were further screened against four different bacteria to assess their selectivity towards MTB. These derivatives could be considered as a precursor structure for further design of antituberculosis agent.
Keywords: 4-dimethylphenylthio)phenyl] aniline; antituberculosis activity; Cytotoxicity; [2-(2

Synthesis and biological evaluation of some new tricyclic pyrrolo[3,2-e]tetrazolo[1,5-c]pyrimidine derivatives as potential antitubercular agents - Patil, Yogesh; Shingare, Ramesh; Choudhari, Amit; Borkute, Rachana; Sarkar, Dhiman; Madje, Balaji R. (Archiv Der Pharmazie, 2018)
A series of new tricyclic pyrrolo[3,2-e]tetrazolo[1,5-c]pyrimidines 8a-l were synthesized and characterized by IR, NMR (H-1 and C-13), and mass spectral analysis. The newly synthesized compounds 8a-l were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra using an established XTT reduction menadione assay (XRMA). The title compounds exhibited minimum inhibitory concentrations (MIC90) ranging from 0.09 to >30g/mL. Five compounds (8c, 8i-l) were further confirmed for their dose-dependent effect against MTB. These compounds were evaluated in the THP-1 infection model, where 8i (MIC90=0.35g/mL), 8j (MIC90=1.17g/mL), 8k (MIC90=2.38g/mL), and 8l (MIC90=1.17g/mL) demonstrated significant antitubercular activity. All the ex vivo active compounds showed insignificant cytotoxicity against the human cancer cell lines, HeLa, MCF-7, and THP-1. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies in the active site of the sterol 14alpha-demethylase (CYP51) enzyme revealed a similar binding mode to the native ligand in the crystal structure, thereby helping to understand the ligand-protein interactions and to establish a structural basis for inhibition of MTB. The results suggest novel pharmacophores as selective and specific inhibitors against MTB that can be explored further to synthesize lead compounds against tuberculosis. In summary, the results clearly indicate the identification of some novel, selective, and specific inhibitors against MTB that can be explored further for potential antitubercular drugs.
Keywords: 2-e]tetrazolo[1; 5-c]pyrimidine; Antituberculosis; Cytotoxicity; Molecular docking; tricyclic pyrrolo[3